Manajemen Keuangan Lembaga Pendidikan Islam (Studi Tafsir Al-Mizan: M. Husain Tabataba’i) - Puspitasari, Fantika Febry; Hamidah, Tutik; Rofiq, Aunur (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2022)
Financial management demandstransparent and accountable financial accountability. To implement it effectively, it is necessary to internalize strong Islamic values. This article examined the principles of financial management in the Qur'an by using the interpretation of al MizanTabataba'i. Theological tendencies in al-Mizan's interpretation were relevant to study financial management which required fundamental principles in Islam. This research employed literature study. The results of the study indicated that Surah Yusuf contained fundamental values in carrying out effective financial management. Surah Yusuf verse 43-49 implied that planning was preceded by an assessment of the condition. Surah Yusuf verse 55 conveyed the characteristics that must be possessed by a person in the financial management. Surah Yusuf verse 59 showed the readiness to face auditing or budget evaluation. This study was supported by Surah Al Ma'un verse 1-3 that in the implementation of financial management of education institution, Islamic education institutions should not ignore orphans and the poor.